Auditing : An integrated Approach - Arens, Alvin A; Loebbecke, James (New Jersey, USA : Prentice-Hall, 1988)
This book is an introduction to auditing for students who have not had significant experience in auditing.
includes index
include index
kjo, 15/01/2019
Loans